THE ENFORCEMENT OF ARBITRAL AWARDS - Suyanto, Suyanto; Situmorang, Nixon; Cavenagh, Thomas (SYNTIFIC, 2024)
Background. According to Law No. 30/1999, Article 60, arbitral awards are binding on the parties, final, and have permanent legal effect. Except in cases of third-party opposition, arbitration rulings do not give rise to legal recourse. Indonesia has been using alternative dispute resolution (ADR) since ancient times. ADR is seen as an alternative to litigation or adjudication. Early neutral evaluation, conciliation, mediation, negotiation, and various hybrid forms are some of the ADR practices Indonesia has been using. Civil procedural law governs the execution of arbitration rulings; these rules are found in the Het Herziene Indonesisch Regelemen or Renewed Indonesian Reglemen. This research aimed to determine the enforcement of arbitral awards. Research Method. This research approach uses a juridical-sociological methodology, which entails researching actual social situations with the goal of fact-finding, which subsequently leads to problem identification, and finally, problem solution. Findings. Similar to the execution of decisions made by civil courts, not all arbitration awards can be carried out due to the challenges involved in doing so. In addition, there must be significant efforts made by seeking for execution seizure of the respondent's property in order to ensure that the obligation to pay a specific sum of money may actually be achieved, ensuring that execution does not become illusory or win on paper alone. Conclusion. Arbitration awards cannot be executed due to challenges and property seizure. Significant efforts are needed to ensure the obligation to pay a specific sum is met, preventing illusory or paper wins.